(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
The idea of conditional sentences and a comparison of the features of speech in Uzbek and English serve as the foundation for this essay. Pupils acquire the concept of sentences in both Uzbek and English. Additionally, they learn about independent sentences, compound-complex sentences, complicated sentences, mixed sentences, exclamatory sentences, interrogative sentences, and conditional sentences. The article’s findings can be used to dissertations, textbooks, manuals, seminars, and lectures on general linguistics, lexicology, comparative linguistics, and linguoculturalology